Key Structural Elements around the East Vietnam Sea (South China Sea) and implications on reconstructions: towards a clarification - Pubellier, M.; Sautter, B. (Vietnam Journal of Marine Science and Technology, 2022)
The East Vietnam Sea (EVS) or the South China Sea (SCS in this paper) is one of the best-studied basins in the world and one of the largest marginal basins. If the mechanisms of rifting and spreading are well documented and invoke many specific aspects of structure and evolution, it has nevertheless been highly controversial in terms of its relationships with the neighboring basins; some of which have partly or entirely disappeared. This paper recapitulates the critical structural elements, such as the localization of magmatic activity and rifted basins from the Cretaceous to the Present, to evaluate the arguments for the reconstructions. We begin with the location of the Cretaceous magmatic arc along the Vietnam and China margins to discuss the setting and timing of the subduction of an oceanic domain which is unlikely to be the Proto South China Sea (PSCS) itself. This evolution raises the question of the existence and modalities of docking of the Argo and Luconia blocks and requires an intensive stretching of this early docked continental basement before seafloor spreading in the PSCS and the Celebes Sea from the end of Cretaceous to the Oligocene. The SCS was the latest basin to open within the continental margin and is believed to have developed within the downgoing plate. The crustal blocks separated by rifting and sea-floor spreading were later shortened from the Early Miocene to the Present, leaving the appearance of a complex tectonic system. This exercise indicates simple solutions which had not been stated previously, such as the possible connection between the Tethys Ocean and an oceanic domain between the PSCS and the coastal regions of China and Vietnam. The PSCS developed later toward the South, probably in a back-arc position, and the EVS opened amid this system intrinsically linked to the subduction of the PSCS.